2017
DOI: 10.4336/2017.pfb.37.90.1189
|View full text |Cite
|
Sign up to set email alerts
|

Emergência de plântulas e crescimento inicial de copaíba sob diferentes substratos

Abstract: O objetivo do trabalho foi avaliar uma emergência e crescimento inicial de mudas de copaíba ( Copaifera langsdorffi Desf.) Sob diferentes substratos. A semeadura foi realizada nos substratos: solo, Bioplant®, solo + areia, solo + Bioplant® e solo + areia + cama-de-frango. Foram avaliadas, velocidade de emergência e crescimento de plântulas. Para uma emergência de plântulas de copaíba são indicados todos os substratos, exceto mistura solo + areia + cama-de-frango. Para o crescimento inicial, indicado pelo índic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…Carnauba residue is a plant residue that presents the physical and chemical characteristics appropriate for the composition of substrates (Araújo et al, 2016). However, Jeromini et al (2017), studying the growth of Copaiba seedlings in substrates formulated with organic compounds, found an effect similar to that presented in this study, whose substrate, formed with soil, obtained an increment in the number of leaves equivalent to soil with a commercial substrate. Also, according to the authors, the results suggest that it is not possible to generalize the beneficial effect of adding organic residues in seedling production and that the results may be contradictory when one works with a given species, since several factors may be involved in obtaining seedlings, such as the required standard of quality.…”
Section: Resultssupporting
confidence: 71%
“…Carnauba residue is a plant residue that presents the physical and chemical characteristics appropriate for the composition of substrates (Araújo et al, 2016). However, Jeromini et al (2017), studying the growth of Copaiba seedlings in substrates formulated with organic compounds, found an effect similar to that presented in this study, whose substrate, formed with soil, obtained an increment in the number of leaves equivalent to soil with a commercial substrate. Also, according to the authors, the results suggest that it is not possible to generalize the beneficial effect of adding organic residues in seedling production and that the results may be contradictory when one works with a given species, since several factors may be involved in obtaining seedlings, such as the required standard of quality.…”
Section: Resultssupporting
confidence: 71%
“…Although they mostly present low nutrient contents and high acidity, many arboreal species manage to develop adequately. Jeromini et al (2017) found higher values in the growth of Copaifera langsdorffii Desf. seedlings in the substrate composed only with soil and Gonçalves et al (2014), testing substrate composed with Argissolo Vermelho-Amarelo, observed that the quantities of nutrients present were sufficient to supply the needs of the jacaranda-da-bahia (Brazilian Rosewood) seedlings.…”
Section: Introductionmentioning
confidence: 84%
“…Atrelado ao uso dos produtos e subprodutos da copaíba e a sua importância, fazse necessário o desenvolvimento de pesquisas sobre as comunidades florestais nas quais a espécie esteja inserida, para que informações acerca do seu adequado manejo possam ser fornecidas. Na literatura é possível encontrar trabalhos que avaliaram características de crescimento, germinação e produção de mudas (JEROMINI et al, 2017;NASCIMENTO et al, 2014;REIS et al, 2016), sobre o uso do óleo e o potencial medicinal da copaíba (MASSON et al, 2013;SANTANA et al, 2014;SOUSA, 2016) e seu potencial na recuperação de áreas antropizadas (OLIVEIRA et al, 2017) Em que: N = número de indivíduos; R = taxa de recrutamento; M = taxa de mortalidade; Tn = taxa de rotatividade em número de árvores; AB = área basal; Decremento = área basal das perdas de fuste e redução diamétrica; Incremento = área basal das árvores sobreviventes; P = taxa de perda; G = taxa de ganho; Tg = taxa de rotatividade em área basal. , 1986;YOUNG, 1994;JUNQUEIRA et al,2000;BREVES-RAMOS et al,2005;FARRAPEIRA, 2006FARRAPEIRA, e 2008.…”
Section: Considerações Finaisunclassified